Profile of the grain physical traits and physicochemical properties of selected Malaysian rice landraces for future use in a breeding program - Site Noorzuraini Abd Rahman; Rosimah Nulit; Faridah Qamaruz Zaman; Khairun Hisam Nasir; Mohd Hafiz Ibrahim; Mohd Ramdzan Othman; Nur Idayu Abd Rahim; Nor Sufiah Sebaweh (AIMS Agriculture and Food)
Malaysia is currently experiencing the same scenario as other countries, as the majority of consumers have shifted their preferences from locally produced rice to imported rice. This has resulted in a significant influx of imported rice into the domestic markets. Food security in the long term cannot be achieved by depending on imported food. Therefore, countries must make an effort to develop high-quality rice to meet the demand of customers. The study aimed to evaluate the grain physical traits and physicochemical properties of 30 Malaysian rice landraces to optimize the use of rice landraces in breeding programs. The grain physical traits were evaluated according to grain size, grain shape, and kernel elongation. Meanwhile, the physicochemical properties were determined by amylose content, alkali spreading value, and gel consistency. The grain length ranged from 4.14 to 8.16 mm and the grain width varied between 1.76 and 2.81 mm. The grain shapes were categorized into three types: medium, long and slender, and bold. Most of the rice landraces exhibited a low amylose content ranging from 16.07 to 19.83, while intermediate amylose content ranged from 20.00 to 23.80. The alkali spreading value showed that most of the rice landraces require an intermediate cooking time. The gel consistency exhibited a wide range, varying from soft to hard. The gel consistency exhibited the highest phenotypic and genotypic coefficient of variance, with values of 42.44% and 41.88%, respectively. Most of the studied traits except for kernel elongation were identified as having high heritability and high genetic advance as a percentage of the mean. A dendrogram effectively revealed the genetic relationships among Malaysian rice landraces by generating three distinct clusters. Cluster Ⅰ was primarily composed of glutinous rice landraces with a low to very low amylose content and exhibited the highest mean values for gel consistency and kernel elongation. Cluster Ⅱ consisted of 13 rice landraces that had the highest mean value for milled grain length and grain shape. Cluster Ⅲ was composed of rice landraces and control rice cultivars, and they exhibited the highest mean values for alkali spreading value, amylose content, and milled grain width. Bokilong, Kolomintuhon, Silou, Tutumoh, and Bidor in Cluster Ⅲ exhibited comparable physicochemical properties and cooking quality traits as the control rice cultivars. The findings of this study are important for identifying potential donors for breeding programs focused on developing high-quality or specialty rice cultivars.